2018
DOI: 10.22190/fueo1803203m
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Psychological Contract Breach on Job Satisfaction

Abstract: Psychological contract represents the implicit assumptions of the employees (or employer) regarding the content of their mutual exchange in addition to those that is specified in the formal employment contract. In the case of breaching it, many negatively consequences could arise. One of them is the lower level of job satisfaction. In the study that has been conducted we tried to find out the answer whether the psychological contract breach in unfavorable economic conditions negatively influences job satisfact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…This would overcome many of the consequences employers may face in dealing with employees so that it goes beyond just employees' job satisfaction to the employees' organizational engagement. In this regard, Milanović et al (2018) found that fulfillment of psychological contracts between employees and employers leads to a positive impact on employees' behavior, as it increases the probability of their satisfaction with their organization. It also drives them to achieve their duties effectively (Liang et al, 2022;Nayak et al, 2021).…”
Section: Psychological Contract Fulfillmentmentioning
confidence: 99%
“…This would overcome many of the consequences employers may face in dealing with employees so that it goes beyond just employees' job satisfaction to the employees' organizational engagement. In this regard, Milanović et al (2018) found that fulfillment of psychological contracts between employees and employers leads to a positive impact on employees' behavior, as it increases the probability of their satisfaction with their organization. It also drives them to achieve their duties effectively (Liang et al, 2022;Nayak et al, 2021).…”
Section: Psychological Contract Fulfillmentmentioning
confidence: 99%
“…These are balanced psychological contract and transitional psychological contract. Balanced psychological contract has the same characteristics as relational psychological contract, but also contains financial elements and transitional psychological contract is form in the period of a crisis or when a company is undergoing some radical organizational change [20]. The most important issue from the employees' perspective is whether their expectations are fulfilled.…”
Section: Types Of Psychological Contractmentioning
confidence: 99%
“…Employment contracts include the involvement of employees and employers and the organization. In contrast to these employment contracts, psychological contracts contain the employee's (or employer's) implicit assumptions regarding the content of their reciprocal exchange other than those specified in the formal employment contract (Milanović et al, 2018). Because they are implicit, psychological contracts do not require documents to be signed, are not binding and do not involve legal aspects.…”
Section: Psychological Contractmentioning
confidence: 99%